Multifunctional antitumor magnetite/chitosan-l-glutamic acid (core/shell) nanocomposites - Santos, Daniela P. [UNESP]; Ruiz, Miguel [UNESP]; Gallardo, Visitacion; Zanoni, Maria Valnice Boldrin [UNESP]; Arias, Jose L. (Springer, 2011)
The development of anticancer drug delivery systems based on biodegradable nanoparticles has been intended to maximize the localization of chemotherapy agents within tumor interstitium, along with negligible drug distribution into healthy tissues. Interestingly, passive and active drug targeting strategies to cancer have led to improved nanomedicines with great tumor specificity and efficient chemotherapy effect. One of the most promising areas in the formulation of such nanoplatforms is the engineering of magnetically responsive nanoparticles. In this way, we have followed a chemical modification method for the synthesis of magnetite/chitosan-l-glutamic acid (core/shell) nanostructures. These magnetic nanocomposites (average size a parts per thousand 340 nm) exhibited multifunctional properties based on its capability to load the antitumor drug doxorubicin (along with an adequate sustained release) and its potential for hyperthermia applications. Compared to drug surface adsorption, doxorubicin entrapment into the nanocomposites matrix yielded a higher drug loading and a slower drug release profile. Heating characteristics of the magnetic nanocomposites were investigated in a high-frequency alternating magnetic gradient: a stable maximum temperature of 46 A degrees C was successfully achieved within 40 min. To our knowledge, this is the first time that such kind of stimuli-sensitive nanoformulation with very important properties (i.e., magnetic targeting capabilities, hyperthermia, high drug loading, and little burst drug release) has been formulated for combined antitumor therapy against cancer.
Keywords: Biodegradable nanoparticle; Cancer; Doxorubicin; Hyperthermia; Magnetically responsive drug nanocarrier; Multifunctional nanoformulation; Nanomedicine